Serum vitamin E as a potential biomarker of sperm velocity in crossbred beef bulls - Alberto Benito Diaz; Purificación Vicente-Galindo; María Anciones-Polo; Mónica Montañés Foz; Raúl Bodas; Juan José García-García; Ainhoa Sarmiento-García (Italian Journal of Animal Science)
Sperm motility is a key determinant of fertility in bulls, with velocity parameters serving as primary indicators of reproductive potential. However, the influence of systemic micronutrients on semen quality remains unclear. This cross-sectional study evaluated the relationship between blood serum concentrations of copper (Cu), selenium (Se), zinc (Zn), vitamin E, and Vitamin A with sperm kinetic traits in 50 healthy Charolais × Limousin bulls (3–5 years old) managed under extensive conditions. Each bull was sampled once for semen and blood. Semen quality was evaluated using a computer-assisted sperm analysis (CASA) system, which provides objective measurement of motility parameters including curvilinear velocity (VCL), straight-line velocity (VSL), and average path velocity (VAP). Serum micronutrient concentrations were measured via standard biochemical assays. Bulls were categorised based on the median progressive motility (PM) value (50.10%) to explore group differences. Bulls above the PM threshold showed significantly higher velocity parameters (VCL, VSL, VAP) and greater serum vitamin E levels (p < 0.05). Conversely, Se concentrations were lower in these bulls (p < 0.05), with no significant differences observed in Cu, Zn, or vitamin A (p > 0.05). Correlation analyses revealed a weak but positive association between vitamin E and sperm velocity (r ≈ 0.21), supporting its potential as a biomarker of semen quality, while selenium showed a negative association with pregnancy outcomes (PM). In contrast, other trace elements showed limited or inconsistent associations. These findings suggest a potential role for systemic vitamin E in reproductive evaluation, although further research is needed to confirm its predictive utility.